ACE2 and LOX enzyme inhibitions of different lavender essential oils and major components linalool and camphor - Biltekin, Sevde Nur; Karadağ, Ayşe Esra; Demirci, Betül; Demirci, Fatih (American Chemical Society, 2022)
In this present study, Lavandula angustifolia, Lavandula stoechas, and Lavandula x heterophylla essential oils and their main compounds linalool and camphor were evaluated in vitro for lipoxygenase enzyme (LOX) and for angiotensin converting enzyme 2 (ACE2) inhibition potential. The chemical compositions of L. angustifolia, L. stoechas, and L. heterophylla essential oils were confirmed both by gas chromatography-mass spectrometry and gas chromatography-flame ionization detection, where 22.4, 0.9, and 30.6% linalool and 17.8, 54.7, and 15% camphor were identified for each oil among other components, respectively. Enzyme inhibitory activity studies were performed at 20 mu g/mL for the tested essential oils, whereas for linalool and camphor concentrations, 5 mu g/mL was used. The ACE2 inhibitions of L. angustifolia, L. stoechas, and L. heterophylla essential oils were 25.4, 34.1, and 27.1%, while the LOX inhibitions were observed as 79, 49.1, and 86.7%, respectively. In addition, linalool and camphor showed remarkable ACE2 inhibition with 77.1 and 85.1%, whereas the LOX inhibition was observed at 92 and 67.2%, respectively. In conclusion of the initial findings, further detailed in vivo studies are needed to confirm the safe use.
Keywords: Antimicrobial Agents; Inhibition; Lipids; Organic Compounds; Peptides and Proteins